The territorial dispute in the Sea of Japan and its impact on regional security - Dimitrijević Duško; Dujić Ivan (Međunarodni Problemi, 2014)
In recent years, the Sea of Japan or the East Sea as it is called in South Korea has become the place of territorial dispute. The territorial dispute between South Korea (Republic of Korea) and Japan refers to the question of sovereignty over the Takeshima/Dokdo Islands. This is a preliminary legal question for resolving the issue of demarcation of marine zones between the countries in dispute. The question of delimitation of marine zones is made particularly difficult by the fact that the countries in dispute have taken unilateral legal acts. Although the specific circumstances regarding the resolution of the territorial dispute differ, both countries see them as an opportunity to secure their geostrategic and then economic interests. Therefore, this dispute like other territorial disputes in Southeast Asia (the South and East China Sea) is the cause of instability, which increasingly threatens peace and security in this part of the world. Under certain internal and external political circumstances, most political factors in the countries use this dispute as an instrument to achieve broader support for their governments. Since territorial disputes relating to the question of state sovereignty, which is usually associated with psychological factors (nationalist feelings and dignity of the people) and historical heritage (which is not in a small number of cases coloured by a heavy imperial or colonial past), none of the parties wants to make concessions to the other side indicating that disputes will not be so easy to resolve and overcome peacefully without the infiltration of external political factors. In the study that follows, the author presents an international legal and political analysis of the territorial dispute in the Sea of Japan with explanations on its impact on the regional security. [Projekat Ministarstva nauke Republike Srbije, br. OI 179023: Srbija u savremenim međunarodnim integrativnim procesima-spoljnopolitički, međunarodni, ekonomski, pravni i bezbednosni aspekti]